2017
DOI: 10.1039/c7cp05565j
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride substitution in LiBH4; destabilization and decomposition

Abstract: Fluoride substitution in LiBH is studied by investigation of LiBH-LiBF mixtures (9 : 1 and 3 : 1). Decomposition was followed by in situ synchrotron radiation X-ray diffraction (in situ SR-PXD), thermogravimetric analysis and differential scanning calorimetry with gas analysis (TGA/DSC-MS) and in situ infrared spectroscopy (in situ FTIR). Upon heating, fluoride substituted LiBH forms (LiBHF) and decomposition occurs, releasing diborane and solid decomposition products. The decomposition temperature is reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…During the thermal decomposition, BH4- ( 2 ) releases hydrogen and forms many possible intermediates (see Figure ). The formation of intermediates, such as normalB2normalH7- ( 4 ) and normalB3normalH8- ( 5 ), facilitate the reverse reactions, due to their weak B−B−B and B−H b −B bonds (normalB3normalH8- ( 5 ): BSO(B−B−B)=0.415, k a (B−B−B)=0.824 mdyn/Å; BSO(B−H b −B)=0.188, k a (B−H b −B)=0.477 mdyn/Å and normalB2normalH7- ( 4 ): BSO(B−B)=0.265, k a (B−B)=0.296 mdyn/Å; BSO(B−H b −B)=0.058, k a (B−H b −B)=0.109 mdyn/Å). The intermediates which facilitate the reverse reactions, such as normalB2normalH7- ( 4 ) and normalB3normalH8- ( 5 ) also show low thermodynamic stability with ΔHfo −24.85 and −27.42 kcal/mol, respectively, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the thermal decomposition, BH4- ( 2 ) releases hydrogen and forms many possible intermediates (see Figure ). The formation of intermediates, such as normalB2normalH7- ( 4 ) and normalB3normalH8- ( 5 ), facilitate the reverse reactions, due to their weak B−B−B and B−H b −B bonds (normalB3normalH8- ( 5 ): BSO(B−B−B)=0.415, k a (B−B−B)=0.824 mdyn/Å; BSO(B−H b −B)=0.188, k a (B−H b −B)=0.477 mdyn/Å and normalB2normalH7- ( 4 ): BSO(B−B)=0.265, k a (B−B)=0.296 mdyn/Å; BSO(B−H b −B)=0.058, k a (B−H b −B)=0.109 mdyn/Å). The intermediates which facilitate the reverse reactions, such as normalB2normalH7- ( 4 ) and normalB3normalH8- ( 5 ) also show low thermodynamic stability with ΔHfo −24.85 and −27.42 kcal/mol, respectively, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of diborane is observed during the thermal decomposition of e. g . LiBH 4 , Mg(BH4)2 , and Mn(BH4)2 . Although diborane has weak B−H b −B bonds ( k a (B−H b −B)=0.904 mdyn/Å, BSO=0.312), the formation of diborane hinder the reversibility of the dehydrogenation reaction due to the loss of boron (B 2 H 6 ( 3 ) is a volatile gas) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chong et al [161] introduced several lanthanide elements fluorides into NaBH 4 , and observed that the 3NaBH 4 -GaF 3 composites displayed a fast kinetics and remained high cycling stability even after 51 cycles. Richter et al [177] reported that milling with LiBF 4 could significantly decrease the decomposition temperature of LiBH 4 , but only diborane gas was released during this process. Zheng et al [178] ball-milled NaBH 4 and Mg(BH 4 ) 2 with fluorographene.…”
Section: Adding Dopantsmentioning
confidence: 99%
“…The heavier halides have provided a wide range of metal borohydride halides with either fully ordered, e.g., KZn(BH 4 ) 2 Cl or Sr(BH 4 )Cl [92,186], partly ordered, e.g., NaY(BH 4 ) 2−x Cl 2+x [187,188], or disordered structures, e.g., K 2 Zn(BH 4 ) x Cl 4−x [189]. The smaller fluoride ion can substitute for the hydride ion, i.e., intramolecular anion substitution, F − → H − , in the BH 4 − complex and the composite NaBH 4 -NaBF 4 provided the first fluorine-substituted borohydride, NaBH 2.1 F 1.9 , observed in the temperature range of 200-215 • C [190,191]. Recently, a new class of Li ion conductors was discovered, LiRe(BH 4 ) 3 Cl, Re = La, Ce, Pr, Nd, Sm, Gd, with an interesting new structure type [115,[192][193][194].…”
Section: Complex Metal Hydrides As Electrolytesmentioning
confidence: 99%